Reviewing knowledge of human resource measurement models: comparing and identifying the strengths and weaknesses - Esmailzadeh, Mona; Sabokro, Mehdi; Khorasgani, Akbar Etebarian (International Journal of Psychosocial Rehabilitation, 2020)
Introduction: Today, the knowledge of how human resources is noticed as a strategic and valuable resource also an asset and providing products and services with good quality and economic, without proper use of this valuable resource is difficult and sometimes impossible. Knowledge is supposed as a strategic asset which can help organizations keep their own competition ability in a mutilated environment, in addition Knowledge and tools to measure it improve the competence of the organization. Purpose: the researchers in this study sought to measure and evaluate the various models of human resources, to compare them and identify the strengths and weaknesses of each. Approach: This article was conducted in 2017 by reviewing domestic and foreign sources and articles in the field of measuring human resource knowledge.The research based on objective is applied research component, based on the nature and methods is the descriptive study, and based on reasoning is inductive approach.. The present study consisted of four stages of implementing the search strategy, collecting articles and their initial review, final review and selection of studies and analysis of articles. Finding: By comparing the measured models, it seemed each of the models dealt with some effective factors on evaluation of knowledge and identified indices measuring knowledge with their certain approaches. Studying indicators presented in a variety of models, and interviews with experts, strengths and weaknesses of each model can be identified which are presented in this research. Conclusion: During studying different models of measuring knowledge indices of each were extracted and then semi-structured interviews with experts, strengths and weaknesses were identified. None of the methods had the ability of identifying reasons and weakness in knowledge status of organization and during measuring process we cannot realize what process improved or declined the final result.